Selected aspects of the structural analysis of the north dome in the "Four Domes Pavilion" = Wybrane aspekty analizy konstrukcyjnej kopuły północnej w pawilonie czterech kopuł - Jasieńko, Jerzy; Raszczuk, Krzysztof; Moczko, Marta; Piechówka-Mielnik, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the paper is north dome of the Four Domes Pavilion in Wroclaw, which was erected according to the project by architect Hans Poelzig in 1913. The geometry of the dome (plan, rise, thickness) has an essential influence on the stress distribution in the structure and may be a crucial factor determining the cracking pattern.
Keywords: Pawilon Czterech Kopuł; kopuła; analiza konstrukcyjna; MES; wzmacnianie; Four Domes Pavilion; dome; strengthening; FEM